Effectiveness of a Group Behavioral Counseling Program in Reducing Depression and Anxiety among Orphaned Teenagers in Care and Protection Homes in Jordan - Al-Ramadin, Naser (Dirasat: Educational Sciences, 2023)
Objectives: The current study aims to investigate the effectiveness of a behavioral counseling program in reducing depression and anxiety among orphaned adolescents in care and protection homes in Jordan. Methods: The study used the quasi-experimental design, in a sample of (30) adolescents, based on their responses to two scales: the depression scale and the anxiety scale. The sample was randomly divided into two equal groups: control and experimental. The experimental group underwent the behavioral counseling program consisting of 12 sessions, while the control group received no treatment. The scales were administered again to both groups, and follow-up measurements were taken for the experimental group. Results: The results showed a significant decrease in post-treatment depression levels for the experimental group (88.53 ± 19.60) compared to the control group (153.13 ± 24.86). Similarly, the study revealed a decrease in post-treatment anxiety levels for the experimental group (96.03 ± 18.37) compared to the control group (153.00 ± 15.78). Furthermore, the study revealed that the effect of counseling for the experimental group lasted for a month and a half in adolescents, and they maintained a low level of depression and anxiety as measured by follow-up. Conclusion: The study highlights the importance of focusing on adolescents in this age group and implementing counseling programs to reduce depression and anxiety levels among them.